G‐protein coupled estrogen receptor, estrogen receptor α, and progesterone receptor immunohistochemistry in the hypothalamus of aging female rhesus macaques given long‐term estradiol treatment. Issue 7 (24th May 2014) - Naugle, Michelle M.; Nguyen, Long T.; Merceron, Tyler K.; Filardo, Edward; Janssen, William G.M.; Morrison, John H.; Rapp, Peter R.; Gore, Andrea C.
ABSTRACT Steroid hormone receptors are widely and heterogeneously expressed in the brain, and are regulated by age and gonadal hormones. Our goal was to quantify effects of aging, long‐term estradiol (E2) treatment, and their interactions, on expression of G protein‐coupled estrogen receptor (GPER), estrogen receptor α (ERα) and progesterone receptor (PR) immunoreactivity in two hypothalamic regions, the arcuate (ARC) and the periventricular area (PERI) of rhesus monkeys as a model of menopause and hormone replacement. Ovariectomized (OVX) rhesus macaques were young (∼11 years) or aged (∼25 years), given oil (vehicle) or E2 every 3 weeks for 2 years. Immunohistochemistry and stereologic analysis of ERα, PR, and GPER was performed. More effects were detected for GPER than the other two receptors. Specifically, GPER cell density in the ARC and PERI, and the percent of GPER‐immunoreactive cells in the PERI, were greater in aged than in young monkeys. In addition, we mapped the qualitative distribution of GPER in the monkey hypothalamus and nearby regions. For ERα, E2 treated monkeys tended to have higher cell density than vehicle monkeys in the ARC. The percent of PR density in the PERI tended to be higher in E2 than vehicle monkeys of both ages. This study shows that the aged hypothalamus maintains expression of hormone receptors with age, and that long‐term cyclic E2 treatment has few effects on their expression, although GPER was affected more than ERα or PR. This result is surprising in light of evidence for E2 regulation of the receptors studied here, and differences may be due to the selected regions, long‐term nature of E2 treatment, among other possibilities. J. Exp. Zool. 321A: 399–414, 2014. © 2014 Wiley Periodicals, Inc.